Anticoagulation and Transjugular Intrahepatic Portosystemic Shunt for the Management of Portal Vein Thrombosis in Cirrhosis: A Prospective Observational Study. (25th July 2021) - Lv, Yong; Bai, Wei; Li, Kai; Wang, Zhengyu; Guo, Wengang; Luo, Bohan; Wang, Jianhong; Wang, Qiuhe; Wang, Enxin; Xia, Dongdong; Li, Xiaomei; Yuan, Jie; et al.
Abstract : INTRODUCTION: Current guidelines recommend anticoagulation as the mainstay of portal vein thrombosis (PVT) treatment in cirrhosis. However, because of the heterogeneity of PVT, anticoagulation alone does not always achieve satisfactory results. This study aimed to prospectively evaluate an individualized management algorithm using a wait-and-see strategy (i.e., no treatment), anticoagulation, and transjugular intrahepatic portosystemic shunt (TIPS) to treat PVT in cirrhosis. METHODS: Between February 2014 and June 2018, 396 consecutive patients with cirrhosis with nonmalignant PVT were prospectively included in a tertiary care center, of which 48 patients (12.1%) were untreated, 63 patients (15.9%) underwent anticoagulation, 88 patients (22.2%) underwent TIPS, and 197 patients (49.8%) received TIPS plus post-TIPS anticoagulation. The decision of treatment option mainly depends on the stage of liver disease (symptomatic portal hypertension or not) and degree and extension of thrombus. RESULTS: During a median 31.7 months of follow-up period, 312 patients (81.3%) achieved partial (n = 25) or complete (n = 287) recanalization, with 9 (3.1%) having rethrombosis, 64 patients (16.2%) developed major bleeding (anticoagulation-related bleeding in 7 [1.8%]), 88 patients (22.2%) developed overt hepatic encephalopathy, and 100 patients (25.3%) died. In multivariate competing risk regression models, TIPS and anticoagulation were associated with a higher probability of recanalization. Long-term anticoagulation using enoxaparin or rivaroxaban rather than warfarin was associated with a decreased risk of rethrombosis and an improved survival, without increasing the risk of bleeding. However, the presence of complete superior mesenteric vein thrombosis was associated with a lower recanalization rate, increased risk of major bleeding, and poor prognosis. DISCUSSION: In patients with cirrhosis with PVT, the individualized treatment algorithm achieves a high-probability recanalization, with low rates of portal hypertensive complications and adverse events.